Molecular characterization of EcCLP1, a new putative cathepsin L protease from Echinococcus canadensis - Naidich, Ariel (2024)
Echinococcus granulosus sensu lato is a platyhelminth parasite and the etiological cause of cysticechinococcosis (CE), a zoonotic and neglected disease that infects animals and humans worldwide. As a part of thebiological arsenal of the parasite, cathepsin L proteases are a group of proteins that are believed to be essential forparasite penetration, immune evasion, and establishment in the tissues of the host. In this work, we have clonedand sequenced a new putative cathepsin L protease from Echinococcus canadensis (EcCLP1). The bioinformatic anal-ysis suggests that EcCLP1 could be synthesized as a zymogen and activated after proteolytic cleavage. The multiplesequence alignment with other cathepsin proteases reveals important functional conserved features like a conservedactive site, an N-linked glycosylation residue, a catalytic triad, an oxyanion hole, and three putative disulfide bonds.The phylogenetic analysis suggests that EcCLP1 could indeed be a cathepsin L cysteine protease from clade 1 as itgrouped with cathepsins from other species in this clade. Modeling studies suggest that EcCLP1 has two domainsforming a cleft where the active site is located and an occluding role for the propeptide. The transcriptomic analysisreveals different levels of cathepsin transcript expression along the different stages of the parasite life cycle. The whole-mount immunohistochemistry shows an interesting superficial punctate pattern of staining which suggests a secretorypattern of expression. The putative cathepsin L protease characterized here may represent an interesting tool for diag-nostic purposes, vaccine design, or a new pharmacological target for antiparasitic intervention.